OPTIMALISASI PENGAMBILAN BARANG DI WAREHOUSE PT. DOK PANTAI LAMONGAN DENGAN SKEMA PERPUTARAN DAN PENYIMPANAN BARANG YANG MENGACU PADAS SISTEM FIFO MENGGUNAKAN TOOLS IDENTIFIKASI PELABELAN BARANG - Firdaus Ilyas Nurdhika; Abdurrahman Faris Indriya Himawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Warehouse is a place for receiving, temporary storage and inventory of sparepart, material and item will be used for production needs. The storage warehouse must have an affective system for maximum retrieval of goods so that it can produce a good goods circulation diagram and good goods storage scheme. PT Dok Pantai Lamongan is a construction company that focuses on new building and ship repair. The FIFO method is one of the appropriate methods to be applied to find out new goods arriving and old goods so that the goods turnover process will be more effective and efficient. This study aims to find out how the process of picking and storing goods is effective and efficient using the FIFO system which refers to the identification tools for picking up goods at PT Dok Pantai Lamongan. The type of research used is descriptive qualitative research. Data collection was carried out by means of interviews, documentation and observation. The results of this study indicate that using the FIFO system using goods identification tools can speed up the circulation of goods and speed up service at the PT Dok Pantai Lamongan warehouse.